Trade Wars and Economic Globalization in Ghana - Darka, Adwoa (American Journal of International Relations, 2024)
Purpose: The aim of the study was to assess the trade wars and economic globalization in Ghana. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: It has been facilitated by advancements in technology, transportation, and communication, enabling companies to operate on a global scale and nations to participate in complex networks of trade and investment. However, alongside globalization, trade wars have emerged as a consequence of geopolitical tensions, protectionist policies, and disputes over trade imbalances and intellectual property rights. These conflicts involve the imposition of tariffs, quotas, and other trade barriers by nations seeking to protect domestic industries or gain leverage in negotiations. Implications to Theory, Practice and Policy: Theory of comparative advantage, hegemonic stability theory and dependency theory may be used to anchor future studies on assessing trade wars and economic globalization in Ghana. Businesses and policymakers should prioritize enhancing risk management practices to navigate the uncertainties and disruptions caused by trade wars effectively. Policymakers should prioritize strengthening multilateral cooperation through forums such as the World Trade Organization (WTO) to uphold the rules-based trading system and prevent the escalation of trade tensions into full-blown trade wars.